Assessment of octopus fisheries management based on fishing technique domain by EAFM (ecosystem approach to fisheries management) in Tarupa Island - Azis, Abd.; Syamsuddin, Haryuna; Yusuf, Muhammad Yusfi; Syamsuarty, Siti; Rismayani, Andi; Sainal, Sainal (Gorontalo State University, 2022)
The increase in the utilization of octopus fishery has made it one of the main commodities of the national fisheries sub-sector. One of the areas that make octopus the main commodity for fishing targets is located on Tarupa Island, Selayar Islands Regency. However, with the increasing market demand for octopuses, the pressure on catching octopus will increase so that it is feared that it will disrupt the octopus's own resources. This study aims to evaluate the management status of octopus fisheries on Tarupa Island using the EAFM (Ecosystem Approach to Fisheries Management) approach in the domain of fishing techniques. The assessment of fisheries management in this study uses a method that refers to the NWG EAFM (National Working Group Ecosystem Approach to Fisheries Management) module. In these various methods, the types of data taken are primary data and secondary data. Analysis of the data used an ordinal-based Likert scoring with scoring assessments of 1, 2, and 3. The greater the value, the better the EAFM fisheries management. The results showed that the management of octopus fisheries on Tarupa Island, Selayar Islands Regency based on the EAFM assessment in the fishing technique domain obtained a composite value of 92 with the category of Very Good status. The majority of all indicators get the maximum scoring value, only the fishery crew certification indicator by the regulations obtains the minimum scoring value